2023
DOI: 10.1093/ibd/izad158
|View full text |Cite
|
Sign up to set email alerts
|

Exclusive Enteral Nutrition Alleviates Th17-Mediated Inflammation via Eliminating Mechanical Stress–Induced Th17-Polarizing Cytokines in Crohn’s-like Colitis

Abstract: Background and Aims Exclusive enteral nutrition (EEN) with a liquid diet is the only established dietary treatment for Crohn’s’ disease (CD). However, the mechanism of action of EEN in CD is unclear. T helper 17 (Th17) immune response plays a critical role in CD. We hypothesized that EEN alleviates Th17 response by eliminating mechanical stress–induced expression of Th17-polarizing cytokines. Methods A rat model of Crohn’s-li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 36 publications
2
6
0
Order By: Relevance
“…Crohn's-like colitis was induced by an intracolonic instillation of TNBS 65 mg/kg in 250 µL of 40% ethanol [12,19]. As reported previously [12,15], this treatment induces transmural and stenotic inflammation mimicking Crohn's disease in the colon. Sham control rats were treated with an intracolonic instillation of 250 µL of saline.…”
Section: Introductionmentioning
confidence: 76%
See 4 more Smart Citations
“…Crohn's-like colitis was induced by an intracolonic instillation of TNBS 65 mg/kg in 250 µL of 40% ethanol [12,19]. As reported previously [12,15], this treatment induces transmural and stenotic inflammation mimicking Crohn's disease in the colon. Sham control rats were treated with an intracolonic instillation of 250 µL of saline.…”
Section: Introductionmentioning
confidence: 76%
“…Other reports demonstrated an improved epithelial permeability [14]. Our recent studies have revealed that EEN may exert its beneficial effects by eliminating mechanical stress and attenuating mechanical stress-induced pro-inflammatory mediators in CD [15]. However, the effect of EEN on the gut microbiome has not been well addressed in these reports.…”
Section: Introductionmentioning
confidence: 90%
See 3 more Smart Citations